Does board composition matter for innovation? A longitudinal study of the organizational slack–innovation relationship in Nasdaq-100 companies - Tim Heubeck; Reinhard Meckl (Journal of Management and Governance, 2023)
In high-tech industries, firms accumulate increasing amounts of excess resources. Existent research paints an ambiguous picture of these slack resources for innovation: while some slack is integral for innovation as fuel for experimentation, too much slack inhibits innovation by causing inefficiencies. However, firms in high-tech industries cannot develop and sustain competitive advantages in the long run without sufficient and steady investments in innovation. Additionally, the increasing complexities within these highly dynamic industries make it easier for managers to pursue their self-interests—often to the organization's detriment. Against this backdrop, the role of the board of directors is particularly crucial in high-tech industries, as it determines the efficacy of the board's governance and resource provisioning functions. This study proposes several board characteristics as moderators of the slack–innovation relationship. The dataset builds on a longitudinal sample of high-tech firms from the Nasdaq-100 Index between 2010 and 2020. The results advance management literature by extending the notion of slack resources as a double-edged sword to high-tech industries. The findings also show that this relationship is contingent on specific board characteristics: larger and more independent boards dampen this relationship, while longer board tenure, more board affiliations, and a larger share of women directors amplify it. Further, the findings caution managers to balance the necessity of slack resources for promoting innovation with its efficiency detriment. The results additionally inform practitioners on determining the optimal board composition in the face of mounting competitive pressures for sustained innovation.
Keywords: 650; Agency theory; Boards of directors; Corporate governance; Innovation; Organizational slack; Resource dependence theory